Virtual reality glasses as a distraction aid and anxiety reduction in a 7-year-old girl who underwent a dental extraction procedure. Case report - Cáceres Matta, Sandra Viviana (2023)
Virtual reality in Pediatric Dentistry has enormous potential, in the treatment of phobia of dental treatments, this technology is also promising, since it shows satisfactory results and in the surgical area it has a high potential for complex treatments, allowing predictable and safe results. However, future studies should have to establish technological standards with high data quality and in the development of applications approved for clinical routine. Distraction is a non-pharmacological pain management technique commonly used by Pediatric Dentists to control pain and anxiety. There are some new techniques that use audio and video stimulation and distract the patient by exposing him to three-dimensional videos. These techniques are called virtual reality audiovisual systems. The objective of this case was to evaluate the effectiveness of virtual reality glasses as a distraction aid to reduce anxiety in a 7-year-old girl who attends the pediatric dentistry office to perform a dental extraction procedure.